Deep Learning as a Tool for Business Language Mastery: A Focus on the Economics Students of Universitas Maarif Hasyim Latif - Nurhidayati, Fitri; Sumrati, Sri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study examines the effectiveness of deep learning strategies in enhancing business language mastery among economics students at Universitas Maarif Hasyim Latif. The primary goal was to assess whether deep learning techniques could improve students' proficiency in business English and their ability to apply the language in real-world business contexts. Using a mixed-methods approach, data were collected through pre- and post-test assessments, surveys, interviews with lecturers, and classroom observations. The results indicated significant improvements in students' business language skills, with an average increase of 18% in language proficiency across various areas, including vocabulary, grammar, writing, listening, and speaking. Additionally, students reported greater confidence in using business English, and lecturers observed higher engagement and critical thinking among students. The study concludes that deep learning strategies are highly effective in enhancing both linguistic and cognitive skills, providing valuable insights for future educational practices in business English instruction